Nitrogen Uptake, Growth and Yield Response of Orange-fleshed Sweet potato (Ipomoea Batatas L.) To Potassium Supply. Issue 2 (19th January 2020) - Wang, Shunyi; Li, Huan; Liu, Qing; Hu, Shuwen; Shi, Yanxi
ABSTRACT: The excessive absorption of nitrogen (N) is easy to cause shoot overgrowth and reduce the root yield of sweet potato. The purpose of this study was to investigate the effects of potassium (K) application on N uptake, growth, and yield of sweet potato. A field experiment with four potassium application treatments (added at rates of 0, 75, 150, and 225 kg ha −1, expressed separately by K0, K75, K150, K225 ) was conducted on the fecund soil at Jiaozhou peninsula of China from 2014 to 2015. The results showed that total N accumulation and dry matter increases with increasing K fertilizer application. K supply reduced leaf and shoot N/K ratio, and increased the N transport rate from 9.8% to 20.1% and root N distribution rate from 50.3% to 59.3% at 150 DAP, and then increased the root dry matter distribution rate, and subsequently increased the yield by 15.3–39.0% of sweet potato. While, K supply improved the efficiency of N absorption and utilization. To enhance the sweet potato yield, K application rate of 150–225 kg ha −1 was identified as optimal.